Hubungan Aktivitas Dengan Hasil Belajar Siswa Di Sekolah Dasar - Mikhyar, Arina; Zuraida, Zuraida; Fachrudin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This type of research is correlational. The population in this study were all fifth grade students of SDN Cluster 1 Pariaman Tengah totaling 106 students. The sample in this study was SDN 17 Kampung Baru, amounting to 20 people. The sampling technique in this study used Cluster Random sampling. The instruments of data collection used were observation sheets and objective question tests. The data analysis technique used by SPSS 16. Computer data analysis techniques consisted of instrument testing, analysis prerequisite test (normality test, linearity test, hypothesis test and coefficient of determination test).From the data analysis performed thevalue is Pearson Correlation 0.873 and r table is 0.468 with a significance level of 5%. The calculation results show that rcount 0.873> rtable 0.468. The significance value obtained is 0,000 <0,05. The determination coefficient of 76.2% is in the strong category. It can be concluded that the activity is very closely related to the integrated thematic learning outcomes of fifth grade students of SD Negeri Gugus 1 Pariaman Tengah.Keywords : Activities, Integrated Thematic, Learning Outcomes.